Factors influencing the adoption of online banking services in Malaysia - Mohamed Zabri, Shafie; Ahmad, Kamilah; Ho, Huay Huay (Advanced science letters, 2018)
Online banking is an electronic payment system that allows customers to conduct financial transaction on a website. However, there are some factors that influencing an individual’s choices on the adoption of online banking services. The objectives of this is to identify the level of online banking adoption and factors influencing the adoption of online banking among Malaysians. The study was based on Technology Acceptance Model (TAM) which has been extended with the inclusion of perceived risks as one of the independent variable. Cluster sampling technique was chosen involving three main villages in Rengam, Johor which are New Village, Taman Sri Jaya and Taman Senda. Self-administered survey with the use of closeended questionnaire was applied in study involving a total of 357 target respondents. A total of 244 questionnaires were returned. Out of this, 237 questionnaires were usable with a response rate of 66.4%. Data was analysed by using Statistical Package for Social Science (SPSS). Findings showed that the level of online banking services adoption is quite low among respondents and all three factors have a significant influence on the level of adoption of online banking among respondents